Efficacy and safety of 25 and 50 μg desmopressin orally disintegrating tablets in Japanese patients with nocturia due to nocturnal polyuria: Results from two phase 3 studies of a multicenter randomized double‐blind placebo‐controlled parallel‐group development program. Issue 1 (9th August 2019) - Yamaguchi, Osamu; Juul, Kristian V.; Falahati, Ali; Yoshimura, Toru; Imura, Futoshi; Kitamura, Mikiya
Abstract: This study assessed the efficacy and safety of desmopressin orally disintegrating tablets (ODTs) in Japanese males (50 and 25 μg) and females (25 μg) with nocturia due to nocturnal polyuria (NP). Two Phase 3 randomized double‐blind placebo‐controlled studies of 342 males and 190 females with nocturia due to NP were conducted. The primary endpoint was change from baseline in mean number of nocturnal voids. In addition, time to first awakening to void, nocturnal urine volume, NP index (NPI), and quality of life were assessed during a 12‐week treatment period. In males, 50 and 25 μg desmopressin ODTs significantly reduced the number of nocturnal voids by −1.21 ( P < .0001) and − 0.96 ( P = .0143), respectively, and significantly prolonged the time to first awakening to void by 117.60 minutes ( P < .0001) and 93.37 minute ( P = .0009), respectively, with no safety concerns. In females, 25 μg desmopressin ODT significantly prolonged the time to first awakening to void by 116.11 minutes ( P = .0257), with no safety concerns. The reduction in the number of nocturnal voids (−1.11) was not significantly different compared with placebo ( P = .0975). Desmopressin ODTs (50 and 25 μg) were an effective and well‐tolerated treatment for nocturia due to NP in Japanese males, and desmopressin ODT 50 μg is an appropriate dose in these patients. For patients who are likely to experience hyponatremia, such as elderly males, starting with 25 μg desmopressin ODT should be considered.